A NARRATIVE REVIEW ON BIOLOGICS IN THE MANAGEMENT OF ASTHMA: ASSESSING THE CURRENT LANDSCAPE. - Santanu Kumar Ghosh (Student's Journal of Health Research, 2023)
Monoclonal antibodies (mAbs) play a crucial role in the treatment of severe asthma. Physicians rely on patient-specific characteristics to determine the appropriate asthma classification for treatment. Currently, there are five biological agents designed to target the 'TH2-high' asthma phenotype, characterized by inflammation primarily driven by type 2 T-helper cells (TH2). This subtype is associated with severe eosinophilic asthma, marked by elevated levels of immunoglobulin E, fractional exhaled nitric oxide (FeNO), and eosinophils. In contrast, the ' TH2-low' asthma phenotype, characterized by increased sputum neutrophil counts and activation of the TH17-mediated interleukin-17 pathway, remains less understood. This review examines the role of mAbs in the management of severe asthma, with a focus on their efficacy in different asthma phenotypes. We analyze existing literature, clinical trials, and studies involving mAbs in severe asthma treatment, particularly those targeting thymic stromal lymphopoietin (TSLP). Biologics targeting 'TH2-high' asthma have shown promising outcomes, effectively reducing symptoms and exacerbations. However, the management of ' TH2-low' asthma remains a challenge due to limited therapeutic options. Recent medical trials have explored the use of mAbs, specifically TSLP-targeting mAbs, which have demonstrated significant efficacy in improving asthma control, even in ' TH2-low' phenotypes. Monoclonal antibodies have revolutionized the treatment of severe asthma, primarily focusing on the ' TH2-high' phenotype. While challenges persist in addressing ' TH2-low' asthma, recent developments, particularly TSLP-targeting mAbs, provide hope for more comprehensive asthma management across various phenotypes. Further research is needed to expand our understanding of ' TH2-low' asthma and explore additional biological agents that may be effective in its treatment. Clinicians should consider personalized treatment approaches, including mAbs, based on the specific asthma phenotype of each patient to optimize asthma management.